Muscle loss: The new malnutrition challenge in clinical practice. Issue 5 (October 2019) - Landi, F.; Camprubi-Robles, M.; Bear, D.E.; Cederholm, T.; Malafarina, V.; Welch, A.A.; Cruz-Jentoft, A.J.
Summary: Recent definitions of malnutrition include low muscle mass within its diagnostic criteria. In fact, malnutrition is one of the main risk factors of skeletal muscle loss contributing to the onset of sarcopenia. However, differences in the screening and diagnosis of skeletal muscle loss, especially as a result of malnutrition in clinical and community settings, still occur mainly as techniques and thresholds used vary in clinical practice. The objectives of this position paper are firstly to emphasize the link between skeletal muscle loss and malnutrition-related conditions and secondly to raise awareness for the timely identification of loss of skeletal muscle mass and function in high risk populations. Thirdly to recognize the need to implement appropriate nutritional strategies for prevention and treatment of skeletal muscle loss and malnutrition across the healthcare continuum. Malnutrition needs to be addressed clinically as a muscle-related disorder and clinicians should integrate nutritional assessment with muscle mass measurements for optimal evaluation of these two interrelated entities to tailor interventions appropriately. The design of monitoring/evaluation and discharge plans need to include multimodal interventions with nutrition and physical exercise that are key to preserve patient's muscle mass and function in clinical and community settings.